Biometric responses of sugarcane under high doses of vinasse - Monalisa S. Costa; Mário M. Rolim; Gerônimo F. da Silva; Djalma E. Simões Neto; José A. Santos Júnior; Ênio F. de F. e Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Rational use of vinasse as a fertilizer in sugarcane cultivation is a good option to increase crop development and yield due to its nutritional support, properly dispose of the by-product, and reduce costs of mineral nutrition. However, in the field, controlling the amount of vinasse can be difficult, interfering in sugarcane development. In this sense, this study aimed to evaluate high doses of vinasse related to biometric responses in the initial growth phase of sugarcane plants. The experimental design was completely randomized, and the treatments consisted of five vinasse doses (0, 150, 300, 600, and 1200 m3 ha-1), with six replicates, except D0, three replicates, and one dose of mineral fertilizer with 70 kg ha-1 of N, 120 kg ha-1 of P2O5 and 90 kg ha-1 of K2O, with three replications. The biometric variables were evaluated in the following sequence: number of tillers per pot from 60 to 150 days after planting (DAP), plant height, number of green and dry leaves from 90 to 210 DAP, stem diameter, leaf area, and fresh and dry biomasses of roots and shoots at 210 DAP. Vinasse increased the biomass production through the number of tillers and the number of leaves compared to mineral fertilizer, promoting greater growth up to the dose of 600 m3 ha-1. The vinasse dose of 1200 m3 ha-1 decreased the plant height.